2018
DOI: 10.1111/are.13677
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fishmeal replacement by Tenebrio molitor meal on growth performance, antioxidant enzyme activities and disease resistance of the juvenile pearl gentian grouper (Epinephelus lanceolatus ♂ × Epinephelus fuscoguttatus ♀ )

Abstract: A 50-day feeding trial was conducted for juvenile pearl gentian grouper (Epinephelus lanceolatus ♂ 9 Epinephelus fuscoguttatus ♀) to determine the optimal amount of Tenebrio molitor meal (TM) that could replace fishmeal (FM) in feeds without reducing growth performance, antioxidant enzyme activities and resistance. Six isonitrogenous and isolipidic diets were formulated with TM replacing 0% FM respectively. Each diet was randomly divided into triplicate groups with 30 juveniles (initial weight 6.60 AE 0.00 g).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 33 publications
4
35
0
Order By: Relevance
“…In addition to the results with other insect species mentioned above, the dietary intake of MW is known to have immunostimulating activity in fish [15,16,17]. Moreover, a 7.5% MW inclusion was reported to enhance Vibrio harveyi resistance in juvenile pearl gentian grouper [12]. Although they concluded that chitin in MW could enhance the immune response in fish, the mechanism is still unknown.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…In addition to the results with other insect species mentioned above, the dietary intake of MW is known to have immunostimulating activity in fish [15,16,17]. Moreover, a 7.5% MW inclusion was reported to enhance Vibrio harveyi resistance in juvenile pearl gentian grouper [12]. Although they concluded that chitin in MW could enhance the immune response in fish, the mechanism is still unknown.…”
Section: Discussionmentioning
confidence: 96%
“…Although this insect appears to possess adequate amino acid profiles for use in fish feed [1,2,3,5,6], reports on the successful complete substitution of fish meal (FM) with MW have been limited. Based on the evidence published to date, a diet with 50% to 70% replacement of FM with dried full-fat mealworm larvae resulted in similar growth to the FM diet in gilthead seabream ( Sparus aurata ) [7], European seabass ( Dicentrarchus labrax ) [8], black spot seabream ( Pagellus bogaraveo ) [9], and rainbow trout ( Oncorhynchus mykiss ) [10,11], and only 12% replacement for FM was achieved with defatted mealworm larvae in pearl gentian grouper ( Epinephelus lanceolatus × Epinephelus fuscoguttatus ) [12]. However, the MW’s potential in diets for red seabream ( Pagrus major Temminck and Schlege) (Perciformes: Sparidae) has not been investigated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, few studies are available on the use of a defatted TM meal. On juvenile pearl gentian grouper, Song et al [42] tested a TM meal with a 65% CP content in a feeding trial that lasted 50 days. The fish were fed up to 31.5 % of graded levels of TM meal and the authors found a lower final weight and WG rate in the control fish and in the 6.25% inclusion level groups, while the FCR of the fish fed 12.5 and 18.75% TM diets showed no significant difference compared to the control diet.…”
Section: Performancementioning
confidence: 99%
“…The fish were fed up to 31.5 % of graded levels of TM meal and the authors found a lower final weight and WG rate in the control fish and in the 6.25% inclusion level groups, while the FCR of the fish fed 12.5 and 18.75% TM diets showed no significant difference compared to the control diet. In order to obtain a maximum WG rate and according to a broken-line model, authors recommended a TM inclusion level of 4.92%, corresponding to a FM substitution of 12.3% [42].…”
Section: Performancementioning
confidence: 99%